Separator for secondary battery and secondary battery comprising same

By using a porous substrate, an inorganic layer and an adhesive layer containing vinylidene fluoride-based polymer particles with different solization temperatures in the lithium battery separator, the problem of degradation of adhesion of the lithium battery separator is solved, and excellent adhesion is achieved and breathability improve battery capacity and safety.

CN119174045APending Publication Date: 2024-12-20SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039482.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-09
Filing Date
2023-05-08
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The adhesion of the separator of the lithium battery during the charge and discharge cycle is reduced, resulting in capacity deterioration and safety reduction, and it is difficult for the prior art to improve adhesion and breathability simultaneously.

Method used

A combined structure of a porous substrate, an inorganic layer and an adhesive layer is adopted, wherein the adhesive layer comprises first vinylidene fluoride-based polymer particles and second vinylidene fluoride-based polymer particles of different solization temperatures to form excellent adhesive Adhesion and breathability.

Benefits of technology

It improves the adhesion and breathability of the lithium battery separator, extends the battery life, enhances safety, and prevents the battery shape from deforming and capacity reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119174045A_ABST
    Figure CN119174045A_ABST
Patent Text Reader

Abstract

Disclosed are a separator for a secondary battery and a secondary battery including the same, the separator comprising: a porous substrate; an inorganic layer disposed on at least one surface of the porous substrate; and an adhesive layer disposed on the inorganic layer, in which the adhesive layer includes first vinylidene fluoride-based polymer particles and second vinylidene fluoride-based polymer particles having different solation temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a separator for a secondary battery and a secondary battery including the separator. Background Art

[0002] The miniaturization and lightness of lithium batteries are important for meeting the miniaturization and high performance of various devices. In addition, the discharge capacity, energy density and cycle characteristics of lithium batteries are important for applications in fields such as electric vehicles. Lithium batteries with large discharge capacity per unit volume, high energy density and high capacity, as well as excellent life characteristics and safety are required to meet the above applications.

[0003] In lithium batteries, the separator is arranged between the positive electrode and the negative electrode to prevent short circuits. The electrode assembly including the positive electrode, the negative electrode and the separator arranged between the positive electrode and the negative electrode is wound into a core shape, and the core is rolled to improve the adhesion between the positive electrode / negative electrode and the separator in the electrode assembly. During this rolling process, the interface resistance between the positive electrode and the separator and the interface resistance between the negative electrode and the separator increase, and therefore, as the charge and discharge cycles of the lithium battery are repeated, the capacity and high-rate charge and discharge characteristics of the lithium battery may deteriorate.

[0004] Therefore, in order to manufacture a lithium battery having high capacity as well as excellent lifespan characteristics and safety, a smaller thickness and reduced weight are required, and thus, a separator having strong adhesion and improved stability is required. Summary of the invention

[0005] Technical issues

[0006] One aspect is to provide a separator for a secondary battery having improved adhesion and stability.

[0007] Another aspect is to provide a secondary battery including the above separator having high capacity, excellent capacity and lifespan characteristics, and improved safety.

[0008] Technical Solution

[0009] According to one aspect, a separator for a secondary battery is provided, the separator comprising a porous substrate, an inorganic layer located on at least one side of the porous substrate, and an adhesive layer located on the inorganic layer, wherein the adhesive layer comprises a first vinylidene fluoride polymer particle and a second vinylidene fluoride polymer particle having different solvation temperatures. The first vinylidene fluoride polymer particle is a first copolymer, the first copolymer comprising a vinylidene fluoride (VDF) repeating unit, a hexafluoropropylene (HFP) repeating unit, and a repeating unit having one or more functional groups selected from a C=O group and an OH group, wherein the solvation temperature of the first copolymer is 85°C or lower, the content of the hexafluoropropylene (HFP) repeating unit is 10 mol% or more, and the content of the repeating unit having one or more functional groups selected from a C=O group and an OH group is 3 mol% or less.

[0010] The second vinylidene fluoride polymer particles are selected from: i) polyvinylidene fluoride particles having a solvation temperature of 100°C or higher; and ii) a second copolymer, the second copolymer having a solvation temperature of 100°C or higher and comprising vinylidene fluoride (VDF) repeating units and hexafluoropropylene (HFP) repeating units, wherein the content of the hexafluoropropylene (HFP) repeating units in the second copolymer is 3 mol% or less.

[0011] Provided is a separator for a secondary battery, wherein first and second vinylidene fluoride-based polymer particles have a size of 200 nm to 1 μm.

[0012] According to another aspect, there is provided a secondary battery including a positive electrode, a negative electrode, and the above-mentioned separator disposed between the positive electrode and the negative electrode.

[0013] Beneficial Effects

[0014] The separator for a secondary battery according to one embodiment includes an adhesive layer with improved adhesion, thereby ensuring excellent adhesion and good air permeability after the bonding process, and having excellent adhesion between the separator and the electrode after charge and discharge, thereby preventing the shape of the battery from being deformed. Therefore, it is possible to provide a secondary battery with improved capacity, life and safety by using the separator. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a schematic diagram showing a cross section of a separator of a lithium battery according to one embodiment.

[0016] Figure 2 is a schematic diagram showing a cross section of a separator of a lithium battery according to another embodiment.

[0017] Figure 3is a schematic diagram showing a cross section of a separator of a lithium battery according to still another embodiment.

[0018] Figure 4 is a schematic diagram of a lithium battery according to one embodiment.

[0019] [Explanation of Reference Numerals]

[0020] 10: diaphragm 20: porous substrate

[0021] 30: Inorganic layer 40: Adhesive layer

[0022] 140: Positive electrode 150: Negative electrode

[0023] 160: Electrode assembly 170: Shell DETAILED DESCRIPTION

[0024] Hereinafter, a separator for a secondary battery and a secondary battery including the same according to embodiments will be described in more detail.

[0025] Lithium secondary batteries generally have a separator arranged between a positive electrode and a negative electrode, and are subjected to a hot pressing process at a certain temperature and pressure. Through the hot pressing process, the adhesion of the interface between the positive electrode and the separator and between the negative electrode and the separator increases, thereby maintaining the shape of the battery. When the adhesion is insufficient, the interface with the electrode bulges, which fundamentally leads to a continuous decrease in capacity according to the cycle of the lithium polymer battery and a degradation of the high-rate charge and discharge characteristics, and reduces the safety of the battery, which needs to be improved.

[0026] Therefore, in order to solve the above problems, the inventors have completed a diaphragm for a secondary battery, the diaphragm having a bonding layer of a first vinylidene fluoride polymer particle and a second vinylidene fluoride polymer particle with different solvation temperatures. Using such an adhesive layer, it is possible to ensure excellent adhesion and air permeability after the bonding process of the secondary battery, improve the adhesion of the adhesive layer to the inorganic layer, and provide a diaphragm with low resistance. As a result, the adhesion strength between the electrode and the diaphragm can be controlled to be greater, thereby manufacturing a lithium secondary battery with stable battery performance without abnormal behavior (such as battery expansion during charge and discharge).

[0027] The first vinylidene fluoride polymer particles (or first particles) are first copolymers containing repeating units of vinylidene fluoride (VDF), repeating units of hexafluoropropylene (HFP), and repeating units having one or more functional groups selected from C=O groups and OH groups, wherein the first copolymer has a solvation temperature of 85° C. or lower, a content of the repeating units of hexafluoropropylene (HFP) is 10 mol% or more, and a content of the repeating units having one or more functional groups selected from C=O groups and OH groups is greater than 0 mol% but not greater than 3 mol%. The second vinylidene fluoride polymer particles (or second particles) are selected from: i) polyvinylidene fluoride particles having a solvation temperature of 100° C. or higher; and ii) a second copolymer having a solvation temperature of 100° C. or higher and containing repeating units of vinylidene fluoride (VDF) and repeating units of hexafluoropropylene (HFP), wherein the content of the repeating units of HFP in the second copolymer is 3 mol% or less.

[0028] The first vinylidene fluoride-based polymer particles and the second vinylidene fluoride-based polymer particles each have a size of 200 nm to 1 μm.

[0029] Based on 100 parts by weight of the total weight of the first vinylidene fluoride polymer particles and the second vinylidene fluoride polymer particles, the content of the second vinylidene fluoride polymer particles is 10 to 90 parts by weight, 20 to 90 parts by weight, 20 to 80 parts by weight, 30 to 80 parts by weight, 40 to 80 parts by weight, 50 to 80 parts by weight, or 50 to 75 parts by weight.

[0030] The weight ratio of the first vinylidene fluoride-based polymer particles to the second vinylidene fluoride-based polymer particles is 5:5 to 2:8.

[0031] As a non-limiting example, in the first copolymer, the repeating unit having one or more functional groups selected from a C═O group and an OH group is at least one selected from the group consisting of (meth)acrylic acid, a derivative of a (meth)acrylate having a hydroxyl group, itaconic acid or a derivative thereof, maleic acid or a derivative thereof, and a hydroxyalkane allyl ether.

[0032] The repeating unit having one or more functional groups selected from C=O group and OH group is, for example, maleic acid. When the first copolymer containing repeating units having one or more functional groups selected from C=O group and OH group is used, the adhesion strength to the electrode facing the adhesive layer can be further increased due to the presence of the above functional groups.

[0033] The first vinylidene fluoride-based polymer particles have a sol-forming temperature of 70 to 85° C., for example, 80 to 82° C. When the sol-forming temperature of the first vinylidene fluoride-based polymer particles is within the above range, the first vinylidene fluoride-based polymer particles may act as a binder during a high temperature pressing process of a battery.

[0034] In the first vinylidene fluoride polymer particles, the content of hexafluoropropylene (HFP) repeating units is 10 mol% to 20 mol%, 12 mol% to 18 mol%, or 13 mol% to 17 mol%, and the content of repeating units having one or more functional groups selected from C=O groups and OH groups is greater than 0 mol% but not greater than 3 mol%, 1 mol% to 3 mol%, or 1 mol% to 2 mol%.

[0035] In the first copolymer, the content of the vinylidene fluoride (VDF) repeating unit may be 79 mol% to 87 mol%, or 80 mol% to 86 mol%, or 82 mol% to 85 mol%. When the content of the vinylidene fluoride (VDF) repeating unit, the content of the HFP repeating unit, and the content of the repeating unit having one or more functional groups selected from the group consisting of C=O and OH are respectively within the above ranges, it is possible to improve adhesion to the electrode and ensure air permeability.

[0036] The first copolymer includes, for example, a vinylidene fluoride (VDF) repeating unit, a hexafluoropropylene (HFP) repeating unit, and a maleic acid repeating unit as a repeating unit having one or more functional groups selected from a C═O group and an OH group.

[0037] According to one embodiment, the content of vinylidene fluoride (VDF) repeating units, the content of hexafluoropropylene (HFP) repeating units, and the content of repeating units having one or more functional groups selected from C=O groups and OH groups are 79 mol% to 87 mol% (especially 84 mol%), 10 mol% to 20 mol% (especially 15 mol%), and 1 mol% to 3 mol% (especially 1 mol%), respectively. Here, the repeating units having one or more functional groups selected from C=O groups and OH groups are, for example, maleic acid repeating units.

[0038] In the second vinylidene fluoride-based polymer particles, the polyvinylidene fluoride particles have a solization temperature of 100 to 150° C., and when the solization temperature is within the above range, the polyvinylidene fluoride particles can act as an organic filler, thereby maintaining good air permeability even after a high-temperature pressing process.

[0039] The second copolymer particles have a solubilization temperature of 100°C to 150°C, or 100°C to 140°C.

[0040] The second vinylidene fluoride-based polymer particles are polyvinylidene fluoride (homopolymer), or have a HFP repeating unit content of 3 mol % or less, 2 mol % or less, or 1 mol % or less.

[0041] In the second copolymer, the content of the vinylidene fluoride (VDF) repeating unit may be 97 mol % or more, for example, 97 mol % to 99 mol %.

[0042] In the second copolymer, when the contents of the vinylidene fluoride (VDF) repeating unit and the hexafluoropropylene (HFP) repeating unit are respectively within the above ranges, the second copolymer can ensure excellent adhesion and electrolyte impregnation properties.

[0043] In the adhesive layer according to one embodiment, the total content of the first vinylidene fluoride polymer particles and the second vinylidene fluoride polymer particles is 10 parts by weight to 98 parts by weight based on 100 parts by weight of the total weight of the adhesive layer. When the content of the first vinylidene fluoride polymer particles is within the above range, the interface resistance between the separator and the electrode is reduced, and thus, a separator with improved adhesion can be manufactured.

[0044] When the adhesive layer contains only the first vinylidene fluoride polymer particles, the adhesiveness is excellent, but the resistance increases due to the sharp increase in air permeability after the high temperature pressing process. When the adhesive layer contains only the second vinylidene fluoride polymer particles, the increase in air permeability after the high temperature pressing process is low, but the adhesiveness decreases.

[0045] In the adhesive layer of the separator according to one embodiment, the first vinylidene fluoride polymer particles and the second vinylidene fluoride polymer particles each have a size of 200nm to 1μm, 200nm to 800nm, 200nm to 600nm, 200nm to 500nm, or 200nm to 300nm. When the first vinylidene fluoride polymer particles and the second vinylidene fluoride polymer particles each have a size within the above range, due to the clogging of the pores of the inorganic layer and the porous substrate, it is possible to prevent the air permeability characteristics from being deteriorated.

[0046] In this specification, the term "size" refers to the particle diameter when the particle to be measured is spherical, and refers to the major axis length when the particle is non-spherical. The particle diameter is, for example, the average particle diameter, and the major axis length is, for example, the average major axis length. The average particle diameter and the average major axis length respectively represent the average value of the measured particle diameters and the average value of the measured major axis lengths.

[0047] In the present specification, the size of particles can be evaluated by using a particle size analyzer, a scanning electron microscope or a transmission electron microscope. As the particle size analyzer, for example, LA-950 laser particle size analyzer of HORIBA can be used.

[0048] The average particle diameter is, for example, an average particle diameter observed with a scanning electron microscope (SEM), and can be calculated as an average value of particle diameters of about 10 to 30 particles by using a SEM image.

[0049] When the particle size is measured by using a particle size analyzer, the average particle size represents D50. D50 refers to the average diameter of particles corresponding to 50 vol% of the cumulative volume in the particle size distribution, and refers to the value of the particle size corresponding to 50% from the smallest particle when the total number of particles in the particle size distribution curve accumulated in the order of the smallest particle size to the largest particle size is 100%.

[0050] D50 can be measured by using a particle size analyzer. Alternatively, D50 can be easily obtained by measuring with a measuring device using dynamic light scattering, analyzing the data, counting the number of particles corresponding to each particle size range, and then calculating therefrom.

[0051] The first and second vinylidene fluoride polymer particles each have a weight average molecular weight of 50,000 to 500,000, for example, 150,000 to 450,000, for example, 300,000 to 450,000. When the first and second vinylidene fluoride polymer particles each have a weight average molecular weight within the above range, the adhesion of the separator is improved.

[0052] The first vinylidene fluoride polymer particles and the second vinylidene fluoride polymer particles are aqueous particles. Since the first vinylidene fluoride polymer particles and the second vinylidene fluoride polymer particles are aqueous particles, the particles can be easily dispersed or dissolved in water, so an adhesive layer can be formed by using an aqueous slurry, which is environmentally friendly to non-aqueous organic solvents.

[0053] In a separator for a secondary battery according to one embodiment, the adhesive layer may further include an additional adhesive binder, such as a fluorine resin, a polyacrylic compound, a (meth) acrylic resin, or any combination thereof. Based on the total weight of the adhesive layer, the content of the additional adhesive binder is 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 0.5 to 3 parts by weight, or 0.5 to 2 parts by weight. When the total content of the additional adhesive binder is within the above range, the bonding force between the electrode and the separator can be effectively controlled to be stronger.

[0054] The adhesive binder may also act as a dispersant.

[0055] In the adhesive binder, the weight average molecular weight of the polyacrylic acid compound is 50,000 to 500,000, for example, 150,000 to 450,000, for example, 300,000 to 450,000. When the weight average molecular weight of the polyacrylic acid compound is within the above range, the adhesion of the separator is improved.

[0056] The polyacrylic acid compound includes, for example, polyacrylic acid, polymethacrylic acid, polyethylacrylic acid, polybutylacrylic acid, polyhexylacrylic acid, polyhydroxyethylmethacrylic acid, polyaminoacrylic acid, or any combination thereof.

[0057] The polyacrylic acid compound (PAA compound) may include AQC commercially available from Sumitomo Corporation.

[0058] Fluorine resin acts as a binder to fix inorganic particles to the porous substrate, while providing excellent adhesion between the porous substrate and one side of the adhesive layer and between the electrode and the other side of the adhesive layer. The fluorine resin as a binder has an average particle size of 100nm to 300nm. When the fluorine resin has an average particle size within the above range, the adhesive layer has very excellent adhesion to the porous substrate. Although the diaphragm is exposed to high temperatures, the binder has high heat resistance and can therefore maintain the matrix form of its network structure.

[0059] The fluorine-based resin has a glass transition temperature (Tg) of 50°C or higher and a weight average molecular weight of 200,000 g / mol to 3,000,000 g / mol, 200,000 g / mol to 2,000,000 g / mol, or 300,000 g / mol to 1,200,000 g / mol. In this specification, the weight average molecular weight may be an average molecular weight measured by using a polystyrene standard using gel permeation chromatography. When the weight average molecular weight of the fluorine-based resin is within the above range, the diaphragm may have excellent adhesion.

[0060] The fluorine resin is polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trichloroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, or any combination thereof. The (meth) acrylic binder is polyacrylate, polymethacrylate, polybutyl acrylate, polyacrylonitrile, or any combination thereof.

[0061] In the vinylidene fluoride-hexafluoropropylene copolymer, the content of the vinylidene fluoride repeating unit may be 90 mol% to 99.5 mol%, 93 mol% to 99 mol%, or 95 mol% to 99 mol%. When the content of the vinylidene fluoride repeating unit is within the above range, the vinylidene fluoride-hexafluoropropylene copolymer can ensure excellent adhesion and electrolyte impregnation.

[0062] The crystallinity of the fluorine-based resin may be 35% to 45%, for example, 38% to 45%, or 40% to 45%. The adhesive separator including the fluorine-based resin having a crystallinity within the above range exhibits excellent adhesion to the substrate.

[0063] When the adhesive layer further includes a (meth)acrylic binder, a mixing weight ratio of the (meth)acrylic binder to the total weight of the first particles and the second particles is 0.01:1 to 1:1, or 0.25:1 to 0.75:1.

[0064] According to another embodiment, the adhesive layer may also include, for example, one or more selected from the group consisting of polyvinyl pyrrolidone, polyvinyl acetate, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose and acrylonitrile-styrene-butadiene copolymer.

[0065] In the following, reference will be made to Figure 1 A separator for a secondary battery according to one embodiment is described in detail.

[0066] The secondary battery is, for example, a lithium secondary battery.

[0067] Reference Figure 1 , a separator 10 for a secondary battery according to one embodiment includes a porous substrate 20 and an inorganic layer 30 disposed on one side of the porous substrate 20 .

[0068] exist Figure 1 In the separator, the inorganic layer 30 is provided on one side of the porous substrate 20, but as Figure 3 As shown in , the inorganic layer 30 may be disposed on both sides of the porous substrate. Figure 1 and Figure 3 In the separator, the adhesive layer 40 is disposed on the inorganic layer 30 .

[0069] The adhesive layer 40 includes first and second vinylidene fluoride-based polymer particles having different solvation temperatures. By including the adhesive layer 40 , the separator 10 may exhibit excellent adhesion and air permeability even after the bonding process.

[0070] The adhesive layer 40 has a thickness of 0.01 μm to 10 μm, 0.01 μm to 4 μm, 0.1 μm to 3 μm, 0.1 μm to 2 μm, or 0.1 μm to 1 μm. When the thickness of the adhesive layer is within the above range, excellent adhesion is exhibited. The thickness of the adhesive layer is measured by using a film thickness meter or using an image obtained after observation with a scanning electron microscope (SEM).

[0071] In a diaphragm according to another embodiment, Figure 2 As shown in FIG. 2 , an inorganic layer 30 may be further formed on the other side of the porous substrate 20 . The inorganic layer 30 disposed on the other side of the porous substrate 20 may have a composition that is the same as or different from that of the inorganic layer 30 disposed on one side of the porous substrate 20 .

[0072] Although not shown in the drawings, a separator according to another embodiment may have a stack structure in which an adhesive layer 40 is disposed on the other side of the porous substrate 20 .

[0073] The inorganic particles contained in the inorganic layer 30 are not particularly limited, and inorganic particles commonly used in the art can be used. Specific examples of the inorganic particles that can be used in the present disclosure may include selected from Al 2 O 3 、SiO 2 , B 2 O 3 , Ga 2 O 3 、TiO 2 SnO 2 , boehmite, BaSO 4 、MgO、Mg(OH) 2 , clay, ZnO, CaO, CeO 2 、NiO、GaO、ZrO2、Y 2 O 3 、SrTiO 3 and BaTiO 3 These can be used alone or in combination of two or more thereof. More specifically, Al 2 O 3 (Aluminum Oxide).

[0074] The size of inorganic particles is, for example, 1 μm to 20 μm, 2 μm to 15 μm, or 3 μm to 12 μm. In this specification, the term "size" refers to the average particle size when the particles are spherical, and refers to the average major axis length when the particles are non-spherical. Average particle size refers to D50 based on volume. The average particle size is measured by using a measuring device such as a laser diffraction method or a dynamic light scattering method. The average particle size is measured by using, for example, a laser scattering particle size distribution meter (e.g., HORIBA, LA-920), and is the value of the median diameter (D50) of the particles corresponding to the cumulative volume from the smallest particle to 50 vol% in the particle size distribution curve. The size of inorganic particles can be evaluated by using a scanning electron microscope or a transmission electron microscope. The average particle size is, for example, the average particle size observed with a scanning electron microscope (SEM), and can be calculated as the average value of the particle size of about 10 to 30 particles by using a SEM image.

[0075] When inorganic particles having the above size are used, the dispersibility and coating processability of the inorganic particles in the inorganic layer can be prevented from deteriorating, and the thickness of the inorganic layer can be appropriately adjusted to enhance the mechanical properties. In addition, the size of the pores generated in the separator is appropriately adjusted to reduce the possibility of internal short circuits during charge and discharge of the battery.

[0076] Based on the total weight of 100 parts by weight of the inorganic layer, the content of the inorganic particles in the inorganic layer is 50 parts by weight to 95 parts by weight, 60 parts by weight to 95 parts by weight, or 75 parts by weight to 95 parts by weight. When the content of the inorganic particles is within the above range, the thermal shrinkage of the diaphragm can be effectively suppressed. When the content of the inorganic particles is within the above range, the heat dissipation characteristics of the inorganic particles can be fully demonstrated, and the thermal shrinkage of the diaphragm can be effectively suppressed.

[0077] The inorganic layer 30 constituting the separator 10 is a heat-resistant layer, and therefore, shrinkage and breakage do not occur at high temperatures, and adhesion to the substrate is improved.

[0078] The thickness of the inorganic layer 30 is 0.01 μm to 10 μm, 0.1 μm to 5 μm, 1 μm to 5 μm, 1 μm to 3 μm, or 1 μm to 2 μm.

[0079] Inorganic layer 30 comprises inorganic particles and binder. As binder, crosslinkable binder, non-crosslinkable binder or any combination thereof can be used. Binder is, for example, non-crosslinkable binder, and its non-limiting example can include polyvinylidene fluoride (PVdF) polymer, polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-butadiene-styrene copolymer, poly (acrylic acid-to-acrylamide-to-2-acrylamido-2-methylpropanesulfonic acid) or its sodium salt, polyacrylamide-acrylic acid-hydroxyethyl acrylic acid copolymer or any combination thereof.

[0080] The polyvinylidene fluoride polymer may be, for example, polyvinylidene fluoride, a vinylidene fluoride copolymer, or a mixture thereof. The vinylidene fluoride copolymer refers to a polymer including 5 wt % or less of repeating units other than vinylidene fluoride repeating units. The vinylidene fluoride copolymer may be, for example, a vinylidene fluoride-hexafluoropropylene copolymer.

[0081] The inorganic layer may further include a cross-linkable binder. By additionally including a cross-linkable binder in the inorganic layer, adhesion to a substrate or an electrode and heat resistance may be further improved.

[0082] Crosslinkable binder refers to the material of the binder that can produce with crosslinked structure by causing crosslinking reaction.Crosslinkable binder can be selected from monomer, oligomer, polymer or their mixture with one or more crosslinkable functional groups.By making crosslinkable binder solidify, not only produce physical and chemical bond between monomer, oligomer or polymer, and also produce physical and chemical bond between the binder produced by crosslinking and the inorganic particles through surface treatment, improve the adhesion to substrate and increase coating density, thereby can prepare thin diaphragm.

[0083] The monomer, oligomer or polymer with one or more functional groups has one or more functional groups selected from the group consisting of acrylate, vinyl, hydroxyl, epoxy, oxaalkyl, oxetane, carboxyl, amine, oxazoline, ester and isocyanate. The monomer, oligomer or polymer with one or more functional groups has 2 or more, 3 or more or 4 or more functional groups.

[0084] The crosslinkable binder may include, for example, one or more acrylates selected from the group consisting of: alkyl (meth)acrylates such as methyl methacrylate and methyl acrylate; difunctional (meth)acrylates such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, di(meth)acrylate of polyoxyethylene / polyoxypropylene copolymers, butanediol di(meth)acrylate, and hexamethylene glycol di(meth)acrylate; Trifunctional (meth)acrylates, such as trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, tri(meth)acrylate of ethylene oxide adduct of glycerol, tri(meth)acrylate of propylene oxide adduct of glycerol, and tri(meth)acrylate of ethylene oxide and propylene oxide adduct of glycerol; polyfunctional (meth)acrylates having four or more functional groups, such as diglycerol hexa(meth)acrylate; polyfunctional urethane acrylates; polyfunctional epoxy acrylates; and polyester acrylates.

[0085] The crosslinkable binder may include, for example, vinyl pyrrolidone, vinyl caprolactam, vinyl imidazole, vinyl methyl acetamide, ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, pentyl vinyl ether, hexyl vinyl ether, heptyl vinyl ether, octyl vinyl ether, nonyl vinyl ether, decyl vinyl ether, cyclohexyl vinyl ether, ethylhexyl vinyl ether, dodecyl vinyl ether, octadecyl vinyl ether, and the like.

[0086] The cross-linkable binder may include, for example, bisphenol, bisphenol A, methylene glycol, ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, heptanediol, octanediol, nonanediol, decanediol, and the like. Examples of monomers, oligomers or polymers having one or more epoxy groups may include: dioxirane, such as dioxirane, dioxirane, dioxirane, dioxirane, dioxirane, dioxirane, dioxirane, dioxirane, dioxirane, and dioxirane; glycidyl ether, such as bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, brominated bisphenol A diglycidyl ether, phenol novolac glycidyl ether, and cresol novolac glycidyl ether; glycidyl ester, such as hexahydrophthalic acid glycidyl ester and dimer acid glycidyl ester; glycidyl amine, such as isocyanuric acid glycidyl ester and tetraglycidyl diaminophenylmethane; linear aliphatic epoxide, such as epoxidized polybutadiene; and alicyclic epoxide, such as 3,4-epoxy-6-methylcyclohexyl methyl carboxylate and 3,4-epoxycyclohexyl methyl carboxylate.

[0087] The crosslinkable binder may include 4,4'-diphenylmethane diisocyanate, toluene diisocyanate, tolylene diisocyanate, diisocyanate), naphthylene diisocyanate, 4,4'-dicyclohexylene methane diisocyanate, cyclohexylene diisocyanate, 3,3'-dimethylphenylene diisocyanate, diphenylmethane diisocyanate, 3,3'-dimethylphenylene methane diisocyanate, 4,6'-xylylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 3,5,5-trimethylcyclohexylene diisocyanate, 1,6-hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, m-xylene diisocyanate, trimethylxylene diisocyanate, p-phenylene diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, trans-1,4-cyclohexyl diisocyanate, etc.

[0088] In addition, the compound represented by Formula 1 may be used as a cross-linkable binder:

[0089] Formula 1

[0090]

[0091] In Formula 1, X 1 To X 3 Each is an oxyethylene group, X 4 is an oxyethylene group or an alkyl group having 1 to 10 carbon atoms, R 1 To R 4are each independently any one functional group selected from the group consisting of a (meth)acrylate group, a hydroxyl group, a carboxyl group, an ester group, a cyanate group, an isocyanate group, an amino group, a thiol group, an alkoxy group having 1 to 10 carbon atoms, a vinyl group, and a heterocyclic group, a1 to a4 are each an integer from 1 to 10, and n 1 to n 3 Each is an integer from 0 to 10, and n 1 to n 4 At least one of is an integer from 1 to 10, provided that: when X 4 When it is oxyethylene, n 4 is an integer from 1 to 10 and m is 1, and when X 4 When it is an alkyl group having 1 to 10 carbon atoms, n 4 is 1 and m is 0.

[0092] The ester group can be represented by -COOR, and the amino group can be represented by -NR a R b Indicates that, R, R a and R b Can be each independently selected from the group consisting of alkyl with 1 to 20 carbon atoms, alkenyl with 2 to 20 carbon atoms, alkynyl with 2 to 20 carbon atoms, cycloalkyl with 3 to 20 carbon atoms, cycloalkenyl with 3 to 20 carbon atoms, cycloalkynyl with 4 to 20 carbon atoms and aryl with 6 to 30 carbon atoms. In addition, the heterocyclic group can be selected from the group consisting of heterocyclic alkyl with 2 to 20 carbon atoms, heterocyclic alkenyl with 3 to 20 carbon atoms, heterocyclic alkynyl with 3 to 20 carbon atoms and heteroaryl with 6 to 20 carbon atoms, and can include heteroatoms selected from N, O and S. The heterocyclic group can include, for example, epoxy, oxetanyl, etc.

[0093] The compound of Formula 1 may include a compound of Formula 2 or Formula 3:

[0094] Formula 2

[0095]

[0096] Formula 3

[0097]

[0098] Among them, in formula 2 and formula 3, R 5 The alkyl group may be an alkyl group having 1 to 10 carbon atoms, n5 to n7 may each be an integer of 1 to 5, and a5 to a12 may each be an integer of 1 to 10.

[0099] The compound of Formula 1 may include, for example, ethoxylated pentaerythritol tetraacrylate or ethoxylated trimethylolpropane triacrylate.

[0100] According to one embodiment, a non-crosslinkable acrylic binder may be used as the binder included in the inorganic layer.

[0101] Based on 100 parts by weight of the total weight of the inorganic layer, the content of the non-crosslinkable binder in the inorganic layer is 1 part by weight to 10 parts by weight, or 1 part by weight to 5 parts by weight. When the content of the non-crosslinkable binder in the inorganic layer is within the above range, excellent heat shrinkage resistance and fracture resistance are achieved.

[0102] The inorganic particles contained in the inorganic layer can be surface treated to react with the crosslinkable binder. For example, the inorganic particles can be surface treated with functional groups that can react with the functional groups of the crosslinkable binder. When the inorganic particles are surface treated, due to the reaction between the functional groups of the inorganic particles and the functional groups of the crosslinkable binder, a crosslinking reaction can occur, and a crosslinking reaction between the functional groups of the inorganic particles can also occur, thereby improving the bonding strength between the inorganic particles and the crosslinkable binder, and improving the adhesion or coating density to the substrate. For example, when the crosslinkable binder has an acrylate functional group, the inorganic particles can be surface treated to have an acrylate group. According to another embodiment, a binder comprising an aqueous crosslinkable reactive acrylamide copolymer can be used as a crosslinkable binder further contained in the inorganic layer. The aqueous crosslinkable reactive acrylamide copolymer comprises two or more crosslinkable reactive groups that are crosslinkable to each other. When it can be used in a single component form without a crosslinking agent, two or more crosslinkable reactive groups can be crosslinked to each other by a self-condensation reaction. Thereby, an inorganic layer of the separator can be formed, and thus a separator having high heat resistance characteristics can be provided.

[0103] The crosslinkable reactive group may include: at least one first functional group selected from carboxyl, amine and isocyanate; and at least one second functional group selected from hydroxyl, epoxy and oxazoline, and a crosslinking reaction may occur between the first functional group and the second functional group. For example, the crosslinkable reactive group may include carboxyl and hydroxyl.

[0104] According to one embodiment, the equivalent ratio of the first functional group to the second functional group may be in the range of 30:70 to 70:30. The equivalent ratio of the first functional group to the second functional group may be, for example, in the range of 35:65 to 65:35, 40:60 to 60:40, or 45:55 to 55:45, for example, about 50:50. When the equivalent ratio of the first functional group to the second functional group is within the above range, the cross-linking reaction between the first functional group and the second functional group may proceed smoothly.

[0105] According to one embodiment, the acrylamide copolymer includes an (N-substituted) amide monomer, and the (N-substituted) amide monomer may include one or more selected from the group consisting of: (meth) acrylamide, N,N-dialkyl (meth) acrylamide (such as N,N-dimethyl (meth) acrylamide, N,N-diethyl (meth) acrylamide, N,N-dipropyl (meth) acrylamide, N,N-diisopropyl (meth) acrylamide, N,N-di(n-butyl) (meth) acrylamide , N,N-di(tert-butyl)(meth)acrylamide, etc.), N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, N-n-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, N-methylolpropane(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-methoxyethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide and N-acryloylmorpholine.

[0106] Based on the total moles of the monomer components constituting the acrylamide copolymer, the content of the (N-substituted) amide monomer is 30 mol% to 90 mol%, 40 mol% to 80 mol%, or 50 mol% to 70 mol%. When an acrylamide copolymer having the (N-substituted) amide monomer content as described above is used, a decomposition temperature characteristic of 200° C. or higher may be exhibited.

[0107] According to one embodiment, the acrylamide copolymer may include: (N-substituted) amide monomers; and one or two or more acrylic monomers selected from the group consisting of: carboxyl-containing monomers, (meth) alkyl acrylate monomers, hydroxyl-containing monomers, isocyanate-containing monomers, oxazoline-containing monomers, multifunctional (meth) acrylate monomers, anhydride-containing monomers, sulfonic acid-containing monomers, phosphoric acid-containing monomers, succinimide monomers, maleimide monomers, itaconimide monomers, cyano-containing monomers, (meth) acrylate aminoalkyl ester monomers, (meth) acrylate alkoxyalkyl ester monomers, epoxy-containing acrylate monomers, acrylate monomers having heterocycles, halogen atoms, silicon atoms, etc., acryloylmorpholine, (meth) acrylates having alicyclic hydrocarbon groups, (meth) acrylates having aromatic hydrocarbon groups, and (meth) acrylates obtained from alcohol derivatives of terpene compounds.

[0108] Here, two or more functional groups capable of cross-linking with each other may exist in the (N-substituted) amide-based monomer and the acrylic-based monomer, or may exist only in the acrylic-based monomer.

[0109] Specific examples of acrylic monomers may include: carboxyl-containing monomers such as acrylic acid, (meth)acrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc.; (meth)acrylic acid alkyl ester monomers such as (meth)acrylic acid alkyl ester monomers having a straight or branched alkyl group containing 1 to 20 carbon atoms in the ester portion thereof, specifically, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, (meth)acrylate, tert-butyl (meth)acrylate, Cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctyl (meth)acrylate, nonadecyl (meth)acrylate, myristyl (meth)acrylate, ) palmityl (meth)acrylate, stearyl (meth)acrylate, tetradecyl (meth)acrylate, etc.; hydroxyl-containing monomers, such as hydroxyalkyl (meth)acrylates, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, (4-hydroxymethylcyclohexyl)methyl (meth)acrylate, etc.; multifunctional (meth)acrylate monomers, such as hexanediol diacrylate (HDDA), tris(meth)acrylate, dimethicone ... Propylene glycol diacrylate (TPGDA), ethylene glycol diacrylate (EGDA), trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxy triacrylate (TMPEOTA), glycerol propoxylated triacrylate (GPTA), pentaerythritol tetraacrylate (PETA) or dipentaerythritol hexaacrylate (DPHA); monomers containing anhydride groups, such as maleic anhydride, itaconic anhydride, etc.; monomers containing sulfonic acid groups, such as 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, (meth)acryloyloxynaphthalenesulfonic acid, etc.; monomers containing phosphoric acid groups, such as [2-(2-hydroxyethyl)acryloyl] phosphate, etc.;Succinimide monomers, such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyhexamethylene succinimide, etc.; maleimide monomers, such as N-cyclohexyl maleimide, N-isopropyl maleimide, N-lauryl maleimide, N-phenyl maleimide, etc.; itaconimide monomers, such as N-methyl itaconimide, N-ethyl itaconimide, etc. itaconimide, N-butyl itaconimide, N-octyl itaconimide, N-2-ethylhexyl itaconimide, N-cyclohexyl itaconimide, N-lauryl itaconimide, etc.; cyano group-containing monomers, such as acrylonitrile, (meth) acrylonitrile, etc.; (meth) acrylate aminoalkyl ester monomers, such as (meth) acrylate aminoethyl, (meth) acrylate N, N-dimethylaminoethyl, (meth) acrylate N, N-dimethylaminoethyl, (meth) acrylate tert-butyl aminoethyl ester, etc.; (meth) alkoxyalkyl acrylate monomers, such as methoxyethyl (meth) acrylate, ethoxyethyl (meth) acrylate, propoxyethyl (meth) acrylate, butoxyethyl (meth) acrylate, ethoxypropyl (meth) acrylate, etc.; epoxy-containing acrylate monomers, such as glycidyl (meth) acrylate, etc.; acrylate monomers having heterocyclic rings, halogen atoms, silicon atoms, etc., such as tetrahydrofurfuryl (meth) acrylate, fluorine-containing (meth) acrylate, silicone (meth) acrylate, etc.; acryloyl morpholine; (meth) acrylates having alicyclic hydrocarbon groups, such as cyclopentyl (meth) acrylate, cyclohexyl (meth) acrylate, isobornyl (meth) acrylate, dicyclopentyl (meth) acrylate, etc.; (meth) acrylates having aromatic hydrocarbon groups, such as phenyl (meth) acrylate, phenoxyethyl (meth) acrylate, etc.; (meth) acrylates obtained from alcohol derivatives of terpene compounds; and the like. The acrylamide copolymer can be used alone or in combination of two or more of the above acrylic monomers. ;

[0110] According to one embodiment, the molar ratio of the (N-substituted) amide monomer to the acrylic monomer is in the range of 1:99 to 99:1, 20:80 to 80:20, 30:70 to 70:30, 40:60 to 60:40, or 50:50. When the molar ratio of the (N-substituted) amide monomer to the acrylic monomer is within the above range, a coating layer of a separator having improved heat resistance can be formed.

[0111] The weight average molecular weight of the acrylamide copolymer is 100,000 g / mol to 1,000,000 g / mol, 150,000 g / mol to 800,000 g / mol, 200,000 g / mol to 700,000 g / mol, or 300,000 g / mol to 600,000 g / mol. When the weight average molecular weight of the acrylamide copolymer is within the above range, a separator having a low shrinkage rate when stored at high temperature can be manufactured.

[0112] The glass transition temperature of the acrylamide-based copolymer may be 150° C. or higher, 150° C. to 300° C., 170° C. to 280° C., or 190° C. to 250° C. When the glass transition temperature of the acrylamide-based copolymer is within the above range, a separator having high heat resistance can be formed.

[0113] The acrylamide-based copolymer may include, for example, acrylic acid-acrylamide-(2-acrylamide)-(2-methylpropanesulfonic acid) copolymer or its salt, water-based cross-linkable reactive polyacrylamide-acrylic acid-hydroxyethyl acrylic acid copolymer, or any combination thereof.

[0114] According to one embodiment, the acrylamide-based copolymer may further include one or more non-acrylic monomers. By further including one or more non-acrylic monomers, the heat resistance of the copolymer and the adhesion to the porous substrate of the separator can be further improved.

[0115] Non-acrylic monomers can be used without particular limitation as long as the monomers are copolymerizable monomers other than the above-mentioned acrylic monomers. The copolymerizable non-acrylic monomers can be, for example, vinyl esters, nitrogen-containing heterocyclic monomers, N-vinyl carboxylic acid amides, lactam monomers, olefin monomers, vinyl ether monomers, aromatic vinyl compounds, olefins or dienes, vinyl ethers, vinyl chloride, sulfonic acid group-containing monomers, imide group-containing monomers, isocyanate group-containing monomers, etc., and one or more of them can be selected.

[0116] Specific examples of non-acrylic monomers may include vinyl esters such as vinyl acetate, vinyl propionate, etc.; nitrogen-containing heterocyclic monomers such as N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(methyl)acryloyl-2-pyrrolidone, N-(methyl)acryloylpiperidine, N-(methyl)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazine-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinyl Alkenyl isoxazole, N-vinylthiazole, N-vinyl isothiazole, N-vinyl pyridazine, etc.; N-vinyl carboxylic acid amide; lactam monomers such as N-vinyl caprolactam, etc.; olefin monomers such as isoprene, butadiene, isobutylene, etc.; vinyl ether monomers such as methyl vinyl ether, ethyl vinyl ether, etc.; aromatic vinyl compounds such as vinyl toluene, styrene, etc.; olefins or dienes such as ethylene, butadiene, isoprene, isobutylene, etc.; vinyl ethers such as vinyl alkyl ethers, etc.; vinyl chloride; sulfonic acid group-containing monomers such as styrene sulfonate, allyl sulfonate, sodium vinyl sulfonate, etc.; imide group-containing monomers such as cyclohexyl maleimide, isopropyl maleimide, etc.; isocyanate group-containing monomers such as (meth) acrylate 2-isocyanate ethyl, etc.; etc. These non-acrylic monomers may be used alone or in combination of two or more thereof.

[0117] The content of the non-acrylic monomer included in the acrylamide copolymer is not particularly limited, provided that the non-acrylic monomer does not impair the aqueous cross-linking reaction characteristics of the acrylamide copolymer and the high heat resistance characteristics of the separator. For example, the content of the non-acrylic monomer may be in the range of 0.1 mol% to 30 mol% based on the total molar number of the monomer components constituting the acrylamide copolymer.

[0118] Based on the total weight of the binder, the content of the acrylamide copolymer is 10wt% to 100wt%, 30wt% to 95wt%, 50wt% to 90wt%, or 60wt% to 80wt%. Within the above range, a composition for forming an inorganic layer of a diaphragm having improved heat resistance and adhesion to a substrate can be provided.

[0119] When both the crosslinkable binder and the non-crosslinkable binder are included, the weight ratio of the crosslinkable binder to the non-crosslinkable binder may be 8: 2 to 2: 8, specifically 3: 7 to 7: 3. When the crosslinkable binder and the non-crosslinkable binder having a weight ratio within the above range are used, a separator having improved adhesion and heat resistance can be manufactured.

[0120] The thickness of the porous substrate is 1 μm to 100 μm, 1 μm to 40 μm, 1 μm to 30 μm, 5 μm to 20 μm, 5 μm to 15 μm, or 5 μm to 10 μm. When a porous substrate having a thickness within the above range is used, a separator having an appropriate thickness can be manufactured, which is thick enough to prevent a short circuit between the positive electrode and the negative electrode of the battery, but not so thick that the internal resistance of the battery is increased.

[0121] The porosity of the porous substrate included in the separator is 5% to 95%, 30% to 80%, for example, 40% to 60%, and the air permeability may be 250sec / 100cc or less, for example, 200sec / 100cc or less, for example, 150sec / 100cc or less. The pore size of the porous substrate in the separator may be 0.01μm to 50μm, 0.01μm to 20μm, or 0.01μm to 10μm. When the porosity, air permeability and pore size of the porous substrate included in the separator are within the above ranges, a porous substrate with excellent mechanical properties can be obtained without increasing the internal resistance of the lithium battery.

[0122] The porous substrate can be a polymer film formed by any one polymer selected from but not limited to the group consisting of: polyolefins, such as polyethylene and polypropylene; polyesters, such as polyethylene terephthalate and polybutylene terephthalate; polyacetals; polyamides; polyimides; polycarbonates; polyetheretherketones; polyaryletherketones; polyetherimides; polyamideimides; polybenzimidazoles; polyethersulfones; polyphenylene oxides; cyclic olefin copolymers; polyphenylene sulfides and polyethylene naphthalate; or mixtures of two or more thereof.

[0123] In one example, the porous substrate may be a polyolefin substrate, and the polyolefin substrate has an excellent shutdown function, which may help improve the safety of the battery. The polyolefin substrate may be, for example, selected from the group consisting of a polyethylene monolayer film, a polypropylene monolayer film, a polyethylene / polypropylene double-layer film, a polypropylene / polyethylene / polypropylene three-layer film, and a polyethylene / polypropylene / polyethylene three-layer film. In another example, the polyolefin resin may include a non-olefin resin other than an olefin resin, or may include a copolymer of an olefin monomer and a non-olefin monomer.

[0124] For the method of manufacturing the diaphragm according to an embodiment, any method available in the art can be used. For example, the diaphragm can be manufactured by preparing a slurry containing inorganic particles, a first binder and optional inorganic particles, applying the slurry to a porous substrate, and then performing a drying and rolling process.

[0125] The method of applying the slurry is not particularly limited, and any method available in the art may be used. For example, the separator may be formed by a method such as printing, pressing, embossing, roller coating, doctor blade coating, brush coating, dip coating, spray coating, or flow coating.

[0126] Before forming the porous adhesive layer on one or both sides of the diaphragm substrate, pretreatment such as sulfonation treatment, grafting treatment, corona discharge treatment, ultraviolet irradiation treatment, plasma treatment or sputtering etching treatment may be optionally performed to improve adhesion with the adhesive layer.

[0127] According to another embodiment of the present disclosure, there is provided a secondary battery including: a positive electrode; a negative electrode; a separator according to one embodiment disposed between the positive electrode and the negative electrode; and an electrolyte.

[0128] The secondary battery may be, for example, a lithium secondary battery such as a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0129] A method of manufacturing a secondary battery according to one embodiment is not particularly limited, and a method generally used in the art may be used.

[0130] Hereinafter, reference will be made to a method of manufacturing a diaphragm according to one embodiment.

[0131] An inorganic layer is disposed on the porous substrate. When the inorganic layer is formed, a coating method, a lamination method, a coextrusion method, etc. may be used. Non-limiting examples of the coating method include roller coating, spin coating, dip coating, flow coating, and spray coating, but are not necessarily limited thereto.

[0132] The inorganic layer can be cured by providing a composition for forming the inorganic layer on a porous substrate and then applying light or heat thereto. The light curing can specifically be ultraviolet curing or far infrared curing, for example, ultraviolet curing. The light curing can include, for example, a 500 mJ / cm 2 Up to 3000mJ / cm 2 , specifically, 500 mJ / cm 2 Up to 2000mJ / cm 2The porous heat-resistant layer is irradiated with light in an amount of . The irradiation time can be 1 minute to 15 hours. After light curing, a uniform cured density can be obtained by subsequent heat treatment, which can be performed at a temperature of about 50°C to about 180°C for 1 hour to 10 hours. In addition, thermal curing can include curing at about 40°C to 120°C, 50°C to 100°C, or 60 to 90°C for 1 hour to 36 hours, in particular, about 5 hours to 24 hours.

[0133] The composition for forming the inorganic layer may include a polymerization initiator for cross-linking the material for forming the cross-linkable binder and / or the cross-linkable binder and the surface-treated inorganic particles.

[0134] The polymerization initiator acts as a curing agent that generates free radicals by heat or light, and can be appropriately selected according to the type of material used to form the crosslinkable binder and the functional groups of the inorganic particles. For example, the initiator can be: a thermal polymerization initiator such as a peroxide, azo, amine, imidazole or isocyanate initiator; or a photopolymerization initiator such as an onium salt or an organic metal salt.

[0135] Subsequently, an adhesive layer composition including a first vinylidene fluoride-based polymer, a second vinylidene fluoride-based polymer, and a solvent is coated on the inorganic layer and dried to form an adhesive layer.

[0136] The adhesive layer composition can be provided in the form of a slurry by including water as a solvent. The composition for forming the first coating may also include an organic solvent, provided that the organic solvent does not damage the aqueous properties. The organic solvent may be an alcohol organic solvent. For example, the organic solvent may include one or more alcohol organic solvents selected from the group consisting of methanol, ethanol, propanol and butanol. By using an alcohol organic solvent, a composition for forming the first coating that is harmless to the body and has excellent drying characteristics can be provided, thereby ensuring mass production without reducing productivity. According to one embodiment, water and an organic solvent may be included in a volume ratio of 100:0 to 60:40, 95:5 to 80:20 or 85:15 to 70:30. Within the above range, a composition for forming the first coating of a diaphragm with improved drying characteristics can be provided.

[0137] After the adhesive layer composition is applied, the solvent is volatilized by drying, and thus, the solvent does not exist in the coating layer of the finally obtained separator.

[0138] The adhesive layer composition may further include one or more adhesive binders selected from fluorine-based resins, polyacrylic compounds, and (meth)acrylic resins.

[0139] The method of coating the adhesive layer composition is not particularly limited, and may include, for example, one or more selected from a positive roll coating method, a reverse roll coating method, a micro-gravure coating method, and a direct metering coating method, but is not necessarily limited to these methods. The coating method may be, for example, a direct metering coating method.

[0140] Drying can be performed by using hot air in a dryer. Drying can be performed, for example, at a temperature of 30°C to 80°C, 35°C to 75°C, 40°C to 70°C, or 45°C to 65°C. Within the above temperature range, a separator having improved bending strength and peel strength can be manufactured.

[0141] A secondary battery according to another embodiment includes a positive electrode, a negative electrode, and the above-described separator disposed between the positive electrode and the negative electrode. The secondary battery is, for example, a lithium secondary battery.

[0142] According to one embodiment, a secondary battery includes an electrode assembly, the electrode assembly includes a positive electrode, a negative electrode and the above-mentioned separator arranged between the positive electrode and the negative electrode, wherein the electrode assembly may be in the form of a wound pole core. By including the above-mentioned separator in the lithium battery, the adhesion between the electrode (positive electrode and negative electrode) and the separator is increased, so that the volume change during the charge and discharge of the lithium battery can be suppressed. Therefore, the degradation of the lithium battery accompanied by the volume change of the lithium secondary battery can be suppressed, thereby improving the life characteristics of the lithium battery.

[0143] The lithium secondary battery can be manufactured, for example, by the following method.

[0144] First, a negative electrode active material, a conductive material, a binder and a solvent are mixed to prepare a negative electrode active material composition. The negative electrode active material composition is directly coated on a metal current collector to manufacture a negative electrode plate. Alternatively, the negative electrode active material composition can be cast on a separate support, and then the film peeled off from the support can be laminated on the metal current collector to manufacture a negative electrode plate. The form of the negative electrode is not limited to the forms listed above, and may have a form other than the forms listed above.

[0145] The negative electrode active material includes a carbon material.

[0146] The carbon material may be crystalline carbon, amorphous carbon, or a mixture thereof. The crystalline carbon may be natural graphite, artificial graphite, graphene, carbon black, fullerene soot, or any combination thereof in an unspecified shape, plate-like, or flaky form.

[0147] Natural graphite is naturally occurring graphite and includes flake graphite, highly crystalline graphite, and microcrystalline or cryptocrystalline (non-crystalline) graphite. Artificial graphite is synthetic graphite made by heating amorphous carbon to high temperatures and includes primary graphite or electrographite, secondary graphite, graphite fibers, etc. Expanded graphite is obtained by inserting a chemical substance such as an acid or a base between the layers of graphite and applying heat thereto to expand the vertical layers of the molecular structure. Graphene includes single-layer graphite or multiple single layers of graphite. Carbon black is a crystalline material with less regularity than graphite, and when heated at about 3000 °C for a long time, carbon black can turn into graphite. Fullerene soot is a carbon mixture including at least 3 wt% of fullerenes, which are polyhedral bundle compounds composed of 60 or more carbon atoms. Crystalline carbon can have a spherical, plate-like, fibrous, tubular, or powdery form.

[0148] Amorphous carbon can be soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbide, calcined coke, polymer carbide, or any combination thereof.

[0149] The negative electrode active material may also include non-carbon materials. For example, the negative electrode active material may include one or more selected from the group consisting of metals capable of forming an alloy with lithium, alloys of metals capable of forming an alloy with lithium, and oxides of metals capable of forming an alloy with lithium.

[0150] For example, the metal capable of forming an alloy with lithium may be Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y alloy (where Y is an alkali metal, alkaline earth metal, group 13 to 16 element, transition metal, rare earth element, or any combination of these elements, but not Si), Sn-Y alloy (where Y is an alkali metal, alkaline earth metal, group 13 to 16 element, transition metal, rare earth element, or any combination of these elements, but not Sn), etc. The element Y may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, or any combination thereof.

[0151] For example, the transition metal oxide may be lithium titanium oxide, vanadium oxide, lithium vanadium oxide, etc.

[0152] For example, the non-transition metal oxide may be SnO 2 、SiO x (0 < x < 2), etc.

[0153] Specifically, the negative electrode active material can be selected from Si, Sn, Pb, Ge, Al, SiO x (0 <x≤2)、SnO y (0 <y≤2)、Li 4 Ti 5 O 12 、TiO 2 、LiTiO 3 and Li 2 Ti 3 O 7 One or more of the group consisting of, but not necessarily limited thereto, and any non-carbon-based negative electrode active material generally used in the art can be used.

[0154] According to one embodiment, the negative electrode active material may be a mixture of the above-mentioned carbon material and non-carbon material or a composite containing the above-mentioned carbon material and non-carbon material. The conductive material may include acetylene black, ketjen black, natural graphite, artificial graphite, carbon black, carbon fiber, metal powder, metal fiber, etc. of copper, nickel, aluminum, silver, etc., and may also include one type of conductive material or a mixture of more than one type of conductive material, such as a polyphenylene derivative, but is not limited thereto, and any conductive material available in the art may be used. In addition, the above-mentioned crystalline carbon material may be added as a conductive material.

[0155] The binder may be vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene, styrene butadiene rubber-based polymer, or any combination thereof, but is not limited thereto, and any binder available in the art may be used.

[0156] The solvent may be N-methylpyrrolidone, acetone, water, etc., but is not limited thereto, and any solvent available in the art may be used.

[0157] The contents of the negative electrode active material, the conductive material, the binder, and the solvent are at levels commonly used in lithium batteries. Depending on the purpose and structure of the lithium battery, one or more of the conductive material, the binder, and the solvent may be omitted.

[0158] Meanwhile, the binder used to manufacture the negative electrode may be the same as the coating composition included in the adhesive layer of the separator.

[0159] Next, the positive electrode active material, the conductive material, the binder and the solvent are mixed to prepare a positive electrode active material composition. The positive electrode active material composition is directly coated on a metal current collector and dried to manufacture a positive electrode plate. Alternatively, the positive electrode active material composition can be cast on a separate support, and then the film peeled off from the support can be laminated on the metal current collector to manufacture a positive electrode plate.

[0160] The positive active material may include one or more selected from the group consisting of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate and lithium manganese oxide, but is not necessarily limited thereto, and any positive active material available in the art may be used.

[0161] For example, a compound represented by any of the following formulae may be used: Li a A 1-b B b D 2 (where 0.90≤a≤1.8, and 0≤b≤0.5); Li a E 1-b B b O 2-c D c (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); LiE 2- b B b O 4-c D c (where 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b B c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Co b B c O 2-α F α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Co b B c O 2-α F 2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b B c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Mn b B c O 2-α F α(where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b B c O 2-α F 2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni b E c G d O 2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1.); Li a Ni b Co c Mn d G e O 2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0.001≤e≤0.1.); Li a NeG b O 2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O 2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a MnG b O 2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 2 G b O 4 (where 0.90≤a≤1.8, 0.001≤b≤0.1); QO 2 ;QS 2 ;LiQS 2 ; V 2 O 5 ;LiV 2 O 5 ;LiIO 2 ;LiNiVO 4 ;Li (3-f) J 2 (PO 4 ) 3 (0≤f≤2);Li (3-f) Fe 2 (PO 4 ) 3(0≤f≤2); and LiFePO 4 .

[0162] In these formulas, A is Ni, Co, Mn, or any combination thereof; B is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or any combination thereof; D is O, F, S, P, or any combination thereof; E is Co, Mn, or any combination thereof; F is F, S, P, or any combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or any combination thereof; Q is Ti, Mo, Mn, or any combination thereof; I is Cr, V, Fe, Sc, Y, or any combination thereof; and J is V, Cr, Mn, Co, Ni, Cu, or any combination thereof.

[0163] Of course, a compound having a coating layer on its surface can be used, or a mixture of the above-mentioned compound and a compound having a coating layer can be used. The coating layer may include a coating element compound of an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxygen-containing carbonate of a coating element, or a hydroxycarbonate of a coating element. The compounds constituting these coating layers may be amorphous or crystalline. The coating elements included in the coating layer may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. For the process of forming the coating layer, any coating method (e.g., spraying, impregnation method, etc.) may be used, as long as the coating method does not adversely affect the physical properties of the positive active material, the surface of the positive active material is coated with a compound including the coating element, and since this is well known to those skilled in the art, a detailed explanation is omitted.

[0164] For example, LiNiO 2 、LiCoO 2 、LiMn x O 2x (x=1 or 2), LiNi 1-x Mn x O 2 (0 <x<1)、LiNi 1-x- y Co x Mn y O 2 (0≤x≤0.5, 0≤y≤0.5), LiFeO 2 、V 2 O 5 , TiS, MoS, etc.

[0165] In the positive electrode active material composition, the conductive material, binder and solvent used may be the same as those in the negative electrode active material composition. At the same time, a plasticizer can be further added to the positive electrode active material composition and / or the negative electrode active material composition to form holes inside the electrode plate.

[0166] The contents of the positive electrode active material, conductive material, conventional binder and solvent are at levels commonly used in lithium batteries. Depending on the use and configuration of the lithium battery, one or more of the conductive material, conventional binder and solvent may be omitted.

[0167] Meanwhile, the binder used to manufacture the positive electrode may be the same as the adhesive layer composition included in the adhesive layer of the separator.

[0168] Next, the above-mentioned separator was arranged between the positive electrode and the negative electrode.

[0169] In an electrode assembly including a positive electrode / separator / negative electrode, the separator arranged between the positive electrode and the negative electrode comprises as described above: a porous substrate; and an adhesive layer disposed on both sides of the porous substrate, wherein the adhesive layer comprises the coating composition for the separator as described above.

[0170] The separator can be prepared separately and arranged between the positive electrode and the negative electrode. Optionally, the electrode assembly core can be prepared by winding the electrode assembly including the positive electrode / separator / negative electrode into the form of a core, accommodating the core in a battery case or a battery bag, pre-charging the core under pressure while thermally softening the core while being accommodated in the battery case or the battery bag, hot rolling the charged core, cold rolling the charged core, and subjecting the charged core to a formation process, which charges and discharges the charged core under pressure.

[0171] Next, prepare the electrolyte.

[0172] The electrolyte can be in liquid or gel form.

[0173] For example, the electrolyte may be an organic electrolyte solution. In addition, the electrolyte may be a solid. For example, the electrolyte may be boron oxide, lithium oxynitride, etc., but is not limited thereto, and any solid electrolyte available in the art may be used. The solid electrolyte may be formed onto the negative electrode by using a method such as sputtering.

[0174] For example, an organic electrolyte solution may be prepared. The organic electrolyte solution may be produced by dissolving a lithium salt in an organic solvent.

[0175] The organic solvent can be any organic solvent commonly used in the art. For example, the organic solvent is propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, methyl propionate, ethyl propionate, propyl propionate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, sulfolane, ethylene dichloride, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a mixture thereof.

[0176] As the lithium salt, any lithium salt available in the art can be used. For example, the lithium salt is LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiCF 3 SO 3 、Li(CF 3 SO 2 ) 2 N、Li(FSO 2 ) 2 N, LiC 4 F 9 SO 3 、LiAlO 2 、LiAlCl 4 、LiN(C x F 2x+1 SO 2 )(C y F 2y+1 SO 2 )(wherein x and y are both natural numbers), LiCl, LiI, or a mixture thereof.

[0177] An example of the secondary battery is a prismatic lithium secondary battery. Figure 4 is an exploded perspective view of a lithium battery according to one embodiment.

[0178] Reference Figure 4 The lithium secondary battery 100 according to one embodiment includes an electrode assembly 160 obtained by winding a separator 110 according to one embodiment between a positive electrode 140 and a negative electrode 150 , and a case 170 in which the electrode assembly 160 is embedded.

[0179] The electrode assembly 160 may be in the form of a core formed by winding the positive electrode 140 and the negative electrode 150 with the separator 110 therebetween. As another example, the electrode assembly 160 may be in the form of a stack in which the separator 110 is stacked multiple times between the positive electrode 140 and the negative electrode 150.

[0180] The positive electrode 140 , the negative electrode 150 , and the separator 110 are impregnated with an electrolyte solution (not shown).

[0181] The lithium secondary battery may be a lithium ion battery. The lithium battery may be a lithium polymer battery.

[0182] The lithium secondary battery may be cylindrical, prismatic, or pouch-shaped.

[0183] Due to its excellent high rate characteristics and life characteristics, lithium batteries are suitable for use in electric vehicles (EVs). For example, lithium batteries are suitable for hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs) and the like.

[0184] The present disclosure will be described in more detail by the following examples and comparative examples. However, the examples are used to illustrate the present disclosure and are not intended to limit its scope.

[0185] Preparation Example 1: Preparation of acrylic copolymer

[0186] Into a 10 L four-necked flask equipped with a stirrer, a thermometer and a cooling tube, distilled water (6361 g), acrylic acid (72.06 g, 1.0 mol), acrylamide (604.1 g, 8.5 mol), potassium persulfate (2.7 g, 0.01 mol), 2-acrylamido-2-methylpropanesulfonic acid (103.6 g, 0.5 mol) and a 5N aqueous sodium hydroxide solution (1.05 equivalents relative to the total amount of 2-acrylamido-2-methylpropanesulfonic acid) were added, and then the operation of reducing the internal pressure to 10 mmHg with a diaphragm pump and returning the internal pressure to normal pressure with nitrogen was repeated three times.

[0187] The reaction was carried out for 12 hours while the temperature of the reaction solution was stably maintained between 65° C. and 70° C. After the reaction solution was cooled to room temperature, the pH of the reaction solution was adjusted to 7 to 8 by using a 25% aqueous ammonia solution. In this way, poly(acrylic acid-co-acrylamide-co-2-acrylamide-2-methylpropanesulfonic acid) sodium salt was prepared. The molar ratio of acrylic acid, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid was 10:85:5. About 10 mL of the reaction solution (reaction product) was taken and the non-volatile component of the reaction solution was measured, and the result was 9.5% (theoretical value: 10%).

[0188] (Manufacturing of diaphragms)

[0189] Example 1: Separator having a stacked structure of bonding layer / inorganic layer / porous substrate / inorganic layer / bonding layer

[0190] First, boehmite (Nabaltec, Japan) having an average size of 300 nm was ground in a bead mill for 2 hours, and an inorganic dispersion of 40 wt % of the ground boehmite (70 wt % of water) was obtained. The acrylic copolymer prepared according to Preparation Example 1 as a non-crosslinkable binder was mixed with the inorganic dispersion so that the amount of boehmite was 95 wt %, and then water was added thereto so that the total solid content was 25 wt %, thereby forming a composition for forming an inorganic layer.

[0191] The prepared composition for forming an inorganic layer was applied to one side of a polyethylene single-layer substrate film with a thickness of 5.5 μm as a porous substrate by using a gravure coating method, and then dried for 10 seconds under the conditions of a drying temperature of 70° C. and a wind speed of 15 m / sec, thereby manufacturing a separator having an inorganic layer with a coating thickness of 2 μm.

[0192] Separately, a first vinylidene fluoride-based polymer (first PVdF particles in Table 1, (a-1)) and a second vinylidene fluoride-based polymer (second PVdF particles in Table 1, (b-1)) were mixed in a weight ratio of 1:1, and then a PAA compound (AQC, Sumittomo) (Mw: about 450,000) was applied thereto at 2 wt % of the total weight ratio, thereby forming an adhesive layer composition.

[0193] The adhesive layer composition was applied to the 7.5 μm thick ceramic diaphragm that had been primarily coated to form an adhesive layer with a thickness of 1 μm, thereby manufacturing a diaphragm. Here, the density of the adhesive layer coated on both sides of the ceramic diaphragm was 1.0 g / m 2 An inorganic layer and an adhesive layer were each formed on the other side of the porous substrate according to the above method, thereby manufacturing a separator having a stacked structure of adhesive layer / inorganic layer / porous substrate / inorganic layer / adhesive layer.

[0194] Example 2

[0195] An adhesive layer and a separator were manufactured in the same manner as in Example 1, except that the weight ratio of the first PVdF particles (a-1) to the second PVdF particles (b-1) was 1:3 instead of 1:1 when preparing the adhesive layer composition.

[0196] Comparative Example 1: Separator having a stacked structure of bonding layer / inorganic layer / porous substrate / inorganic layer / bonding layer

[0197] An adhesive layer composition was formed in the same manner as in Example 1 to form an adhesive layer, and a diaphragm having the formed adhesive layer was manufactured, except that when preparing the adhesive layer composition, the PVdF particles (c) and the second PVdF particles (b-1) were mixed in a weight ratio of 1:1 instead of mixing the first PVdF particles (a-1) and the second PVdF particles (b-1) in a weight ratio of 1:1.

[0198] Reference Example 1

[0199] The adhesive layer composition was formed in the same manner as in Example 1 to form an adhesive layer, except that when preparing the adhesive layer composition, the first PVdF particles (a-2) and the second PVdF particles (b-2) were mixed in a weight ratio of 1:1 instead of mixing the first PVdF particles (a-1) and the second PVdF particles (b-1) in a weight ratio of 1:1, and a diaphragm having the formed adhesive layer was manufactured.

[0200] Comparative Example 2

[0201] The bonding layer composition was formed in the same manner as in Example 1 to form a bonding layer, and a diaphragm having the formed bonding layer was manufactured, except that when preparing the bonding layer composition, only the first PVdF particles (a-1) were added and mixed instead of mixing the first PVdF particles (a-1) and the second PVdF particles (b-1) in a weight ratio of 1:1.

[0202] Comparison Example 3

[0203] The bonding layer composition was formed in the same manner as in Example 1 to form a bonding layer, and a diaphragm having the formed bonding layer was manufactured, except that only the PVdF particles (c) were added and mixed instead of mixing the first PVdF particles (a-1) and the second PVdF particles (b-1) in a weight ratio of 1:1.

[0204] Comparison Example 4

[0205] The bonding layer composition was formed in the same manner as in Example 1 to form a bonding layer, and a diaphragm having the formed bonding layer was manufactured, except that only the second PVdF particles (b-1) were added and mixed instead of mixing the first PVdF particles (a-1) and the second PVdF particles (b-1) in a weight ratio of 1:1.

[0206] Table 1

[0207]

[0208] In Table 1, PVDF a-1 and a-2 are XPH-883 commercially available from Solvay, PVDF c is RC10,279 commercially available from Arkema, and PVDF b-1 and b-2 are XPH-838LCS commercially available from Solvay. In Table 1, the solubilization temperature of each PVDF was evaluated according to the following method.

[0209] The electrolyte solution (1M LiBF 4 In propylene carbonate (PC)) is added to each PVDF and mixed with it to pretreat the PVDF. PVDF and electrolyte solution are mixed in a weight ratio of 1:5. The pretreated PVDF is measured by DSC (differential scanning calorimetry). The measurement using DSC is carried out at 25°C to 150°C, and the scanning rate is 10°C / min. The solubilization temperature of PVDF evaluated according to this method represents the actual behavior temperature of PVDF under the electrolyte solution.

[0210] Table 2 summarizes the compositions of PVDF used in the adhesive layer compositions of Examples 1 to 2, Reference Example 1, and Comparative Examples 1 to 4.

[0211] Table 2

[0212]

[0213] (Manufacturing of lithium secondary batteries)

[0214] Manufacturing Example 1

[0215] (Manufacturing of negative electrode)

[0216] The negative electrode was manufactured according to the following process.

[0217] 97wt% of graphite particles with an average particle size of 25μm, 1.5wt% of styrene-butadiene rubber (SBR) binder and 1.5wt% of carboxymethyl cellulose (CMC) were mixed, and the mixture was added to distilled water and stirred for 60 minutes using a mechanical stirrer to prepare a negative active material slurry. The slurry was applied to a 10μm thick copper current collector using a doctor blade, dried at 100°C for 0.5 hours in a hot air dryer, dried again under vacuum and 120°C for 4 hours, and then rolled to prepare a negative electrode.

[0218] (Manufacturing of positive electrode)

[0219] Separately, a positive electrode was manufactured according to the following process.

[0220] 97wt% LiCoO 2, 1.5wt% of carbon black powder as a conductive material and 1.5wt% of polyvinylidene fluoride (PVdF) were mixed, the mixture was added to N-methyl-2-pyrrolidone solvent and stirred for 30 minutes using a mechanical stirrer to prepare a positive active material slurry. The slurry was applied to a 20μm thick aluminum current collector using a scraper, dried at 100°C for 0.5 hours in a hot air dryer, dried again under vacuum and 120°C for 4 hours, and then rolled to manufacture a positive electrode.

[0221] (Electrode assembly core)

[0222] The separator obtained according to Example 1 was arranged between the positive electrode and the negative electrode manufactured as described above, and then a winding process was applied thereto, thereby preparing an electrode assembly core. The core was inserted into a bag, an electrolyte solution was injected therein, and then the bag was vacuum-sealed.

[0223] The electrolyte solution used was a 1.3 M LiPF 6 Dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a volume ratio of 3:5:2.

[0224] The electrode core inserted into the bag was heated at 80°C and 11.7 kgf / cm 2 The lithium battery was manufactured by pressing the battery with a pressure of 1000 μm for 3 minutes.

[0225] Manufacturing Example 2

[0226] A lithium battery was manufactured in the same manner as in Manufacturing Example 1, except that the separator of Example 2 was used instead of the separator of Example 1.

[0227] Comparative Manufacturing Examples 1 to 4

[0228] A lithium battery was manufactured in the same manner as in Manufacturing Example 1, except that the separators of Comparative Examples 1 to 4 were used instead of the separator of Example 1.

[0229] Reference Manufacturing Example 1

[0230] A lithium battery was manufactured in the same manner as in Manufacturing Example 1, except that the separator of Reference Example 1 was used instead of the separator of Example 1.

[0231] Evaluation Example 1: Breathability

[0232] For the separators according to Example 1, Example 2, Comparative Example 1, Reference Example 1, and Comparative Examples 2 to 4, the unit thickness of each separator was measured according to the following method by using an air permeometer (Asahi Seiko OKEN type air permeability tester: EGO1-55-1MR).

[0233] 10 samples were prepared by cutting the membrane into 10 circles each having a diameter of 1 inch at 10 different points of the membrane, and then the time for 100cc of air to pass through each sample was measured using an air permeability measuring device ASAHI SEIKO OKEN type air permeation tester EG01-55-1MR (Asahi Seiko). The time was measured five times each, and then the average value thereof was calculated to measure air permeability.

[0234] For the air permeability measurement device, the setting conditions are as follows: the measurement pressure is 0.05mPa; the cylinder pressure is 2.5kg / cm 2 ; The time is set to 10 seconds; and the average value of the data is obtained by measuring the air permeability of a sample having a length of 1 m 10 times or more at intervals of 10 cm.

[0235] In Table 3, Δ air permeability (sec / 100 cc) indicates a value obtained by subtracting the initial air permeability from the air permeability after bonding.

[0236] Evaluation Example 2: Electrode Adhesion (Wet Adhesion)

[0237] A positive electrode was arranged on one side of each separator manufactured in Example 1, Example 2, Comparative Example 1, Reference Example 1, and Comparative Examples 2 to Comparative Examples 4, and a polyethylene nonwoven fabric was arranged on the other side of the separator, and bonding was performed at about 80° C. for 1 hour under the condition of 300 kgf / cm, thereby manufacturing a unit cell. An electrolyte solution was provided to the unit cell. As the electrolyte solution, a solution of 1 M LiBF 4 Dissolved in propylene carbonate (PC).

[0238] For the positive electrode, LiCoO 2 , polyvinylidene fluoride and carbon black as a conductive material are mixed to prepare a mixture, and the mixture is uniformly dispersed by removing bubbles from the mixture using a mixer to prepare a slurry for forming a positive electrode active material layer. A solvent, N-methyl 2-pyrrolidone are added to the mixture, and the mixing ratio of the composite positive electrode active material, polyvinylidene fluoride and carbon black is 98:1:1 by weight. The slurry prepared according to the above process is applied to an aluminum foil by using a scraper to form a thin electrode plate, which is then dried at 135°C for 3 hours or more, and then subjected to a rolling and vacuum drying process to manufacture a positive electrode.

[0239] Subsequently, adhesion of the unit cell was performed under conditions of about 80° C. and 300 kgf / cm for 1 hour. Thereafter, the unit cell was disassembled and wet adhesion was evaluated by a peel test between the separator and the positive electrode, and the evaluation results are listed in Table 3.

[0240] Table 3

[0241]

[0242] Referring to Table 3, it is found that the air permeability of the separators of Examples 1 and 2 is improved after bonding compared with the separators of Reference Example 1 and Comparative Examples 2 and 3. As can be seen in Table 3, the separator of Comparative Example 2 has excellent wet adhesion, but poor air permeability after bonding. In addition, as shown in Table 3, the separators of Comparative Examples 1 and 4 have good air permeability after bonding, but poor adhesion between the electrode and the substrate of the separator, so it is difficult to obtain a large bonding strength between the electrode and the bonding layer.

[0243] In the above description, the embodiments have been described with reference to the accompanying drawings and examples, but the embodiments are only examples, and those skilled in the art will appreciate that various modifications and other equivalent embodiments are possible. Therefore, the protection scope of the present disclosure should be determined by the appended claims.

[0244] Although the embodiments are described above with reference to preparation examples, it will be understood by those skilled in the art that various modifications and changes may be made without departing from the spirit and scope of the appended claims.

Claims

1. A separator for a secondary battery, the separator comprising: porous substrate; an inorganic layer disposed on one side of the porous substrate; and an adhesive layer disposed on the inorganic layer, The adhesive layer includes first vinylidene fluoride polymer particles and second vinylidene fluoride polymer particles having different solvation temperatures.

2. The separator for a secondary battery according to claim 1, wherein The first vinylidene fluoride-based polymer particles are a first copolymer including a vinylidene fluoride repeating unit, a hexafluoropropylene repeating unit, and a repeating unit having one or more functional groups selected from a C═O group and an OH group.

3. The separator for a secondary battery according to claim 2, in, The content of the hexafluoropropylene repeating unit is 10 mol% or more, and the content of the repeating unit having one or more functional groups selected from a C═O group and an OH group is greater than 0 mol% but not greater than 3 mol%.

4. The separator for a secondary battery according to claim 1, in, The first copolymer has a solubilization temperature of 85° C. or lower.

5. The separator for a secondary battery according to claim 1, in, The second vinylidene fluoride polymer particles are selected from: i) polyvinylidene fluoride particles having a solubilization temperature of 100° C. or higher; and ii) A second copolymer having a solubilization temperature of 100° C. or higher and comprising a vinylidene fluoride repeating unit and a hexafluoropropylene repeating unit.

6. The separator for a secondary battery according to claim 1, in, The content of the hexafluoropropylene repeating unit in the second copolymer is 3 mol% or less.

7. The separator for a secondary battery according to claim 1, in, The first vinylidene fluoride-based polymer particles and the second vinylidene fluoride-based polymer particles have a size of 200 nm to 1 μm.

8. The separator for a secondary battery according to claim 1, in, The repeating unit having one or more functional groups selected from C═O group and OH group of the first copolymer includes at least one selected from the group consisting of (meth)acrylic acid, a derivative of (meth)acrylic acid ester having a hydroxyl group, itaconic acid or a derivative thereof, maleic acid or a derivative thereof, and hydroxyalkane allyl ether.

9. The separator for a secondary battery according to claim 1, in, The second vinylidene fluoride-based polymer particles may be included in an amount of 10 to 90 parts by weight based on 100 parts by weight of the total weight of the first and second vinylidene fluoride-based polymer particles.

10. The separator for a secondary battery according to claim 1, in, The first vinylidene fluoride polymer particles have a solubilization temperature of 70 to 85° C., a hexafluoropropylene repeating unit content of 10 to 20 mol %, and a repeating unit having one or more functional groups selected from C═O groups and OH groups content of 1 to 3 mol %.

11. The separator for a secondary battery according to claim 1, in, The second vinylidene fluoride polymer particles have a solubilization temperature of 100°C to 150°C.

12. The separator for a secondary battery according to claim 1, in, The total content of the first vinylidene fluoride-based polymer particles and the second vinylidene fluoride-based polymer particles in the adhesive layer is 10 parts by weight to 98 parts by weight based on 100 parts by weight of the total weight of the adhesive layer.

13. The separator for a secondary battery according to claim 1, in, The separator further includes: an adhesive layer or an inorganic layer disposed on the other side of the porous substrate.

14. The separator for a secondary battery according to claim 1, in, The separator further includes: an adhesive layer disposed on the other side of the porous substrate; and an inorganic layer disposed between the adhesive layer disposed on the other side of the porous substrate and the porous substrate.

15. The separator for a secondary battery according to claim 1, in, The adhesive layer further includes one or more adhesive binders selected from fluorine-based resins, polyacrylic compounds, and (meth)acrylic resins.

16. The separator for a secondary battery according to claim 1, in, The inorganic layer includes inorganic particles and a binder. The inorganic particles are Al2O3, SiO2, B2O3, Ga2O3, TiO2, SnO2, boehmite, BaSO4, MgO, Mg(OH)2, clay, ZnO, CaO, CeO2, NiO, GaO, ZrO2, Y2O3, SrTiO3, BaTiO3, or any combination thereof.

17. The separator for a secondary battery according to claim 16, in, The binder is a polyvinylidene fluoride polymer, polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-butadiene-styrene copolymer, poly(acrylic acid-co-acrylamide-co-2-acrylamido-2-methylpropane sulfonic acid) or its sodium salt, polyacrylamide-acrylic acid-hydroxyethyl acrylic acid copolymer, or any combination thereof.

18. The separator for a secondary battery according to claim 16, in, The inorganic particles may be included in an amount of 50 to 95 parts by weight based on 100 parts by weight of the total weight of the inorganic layer. 19 . A secondary battery comprising a positive electrode, a negative electrode, and the separator according to claim 1 disposed between the positive electrode and the negative electrode.